A shift in energy metabolism anticipates the onset of sarcopenia in rhesus monkeys. Issue 4 (27th May 2013) - Pugh, Thomas D.; Conklin, Matthew W.; Evans, Trent D.; Polewski, Michael A.; Barbian, Hannah J.; Pass, Rachelle; Anderson, Bradley D.; Colman, Ricki J.; Eliceiri, Kevin W.; Keely, Patricia J.; Weindruch, Richard; Beasley, T. Mark; et al.
Summary: Age‐associated skeletal muscle mass loss curtails quality of life and may contribute to defects in metabolic homeostasis in older persons. The onset of sarcopenia occurs in middle age in rhesus macaques although the trigger has yet to be identified. Here, we show that a shift in metabolism occurs in advance of the onset of sarcopenia in rhesus vastus lateralis . Multiphoton laser‐scanning microscopy detects a shift in the kinetics of photon emission from autofluorescent metabolic cofactors NADH and FAD. Lifetime of both fluorophores is shortened at mid‐age, and this is observed in both free and bound constituent pools. Levels of FAD and free NADH are increased and the NAD/NADH redox ratio is lower. Concomitant with this, expression of fiber‐type myosin isoforms is altered resulting in a shift in fiber‐type distribution, activity of cytochrome c oxidase involved in mitochondrial oxidative phosphorylation is significantly lower, and the subcellular organization of mitochondria in oxidative fibers is compromised. A regulatory switch involving the transcriptional coactivator PGC‐1α directs metabolic fuel utilization and governs the expression of structural proteins. Age did not significantly impact total levels of PGC‐1α; however, its subcellular localization was disrupted, suggesting that PGC‐1α activities may be compromised. Consistent with this, intracellular lipid storage is altered and there is shift to larger lipid droplet size that likely reflects a decline in lipid turnover or a loss in efficiency of lipid metabolism. We suggest that changes in energy metabolism contribute directly to skeletal muscle aging in rhesus monkeys.